FISH-Based Markers Enable Identification of Chromosomes Derived From Tetraploid Thinopyrum elongatum in Hybrid Lines - Li, Daiyan; Li, Tinghui; Wu, Yanli; Zhang, Xiaohui; Zhu, Wei; Wang, Yi; Zeng, Jian; Xu, Lili; Fan, Xing; Sha, Lina; Zhang, Haiqin; Zhou, Yonghong; et al. (Frontiers in Plant Science, 2018)
Tetraploid Thinopyrum elongatum, which has superior abiotic stress tolerance characteristics, and exhibits resistance to stripe rust, powdery mildew, and Fusarium head blight, is a wild relative of wheat and a promising source of novel genes for wheat improvement. Currently, a high-resolution fluorescence in situ hybridization (FISH) karyotype of tetraploid Th. elongatum is not available. To develop chromosome-specific FISH-based markers, the hexaploid Trititrigia 8801 and two accessions of tetraploid Th. elongatum were characterized by different repetitive sequences probes. We found that all E-genome chromosomes could be unambiguously identified using a combination of pSc119.2, pTa535, pTa71, and pTa713 repeats, and the E-genome chromosomes of the wild accessions and the partial amphiploid failed to exhibit any significant variation in the probe hybridization patterns. To verify the validation of these markers, the chromosome constitution of eight wheat- Th. elongatum hybrid derivatives were analyzed. We revealed that these probes could quickly detect wheat and tetraploid Th. elongatum chromosomes in hybrid lines. K16-712-1-2 was a 1E (1D) chromosome substitution line, K16-681-4 was a 2E disomic chromosome addition line, K16-562-3 was a 3E, 4E (3D, 4D) chromosome substitution line, K15-1033-8-2 contained one 4E, two 5E, and one 4ES•1DL Robertsonian translocation chromosome, and four other lines carried monosomic 4E, 5E, 6E, and 7E chromosome, respectively. Furthermore, the E-genome specific molecular markers analysis corresponded perfectly with the FISH results. The developed FISH markers will facilitate rapid identification of tetraploid Th. elongatum chromosomes in wheat improvement programs and allow appropriate alien chromosome transfer.